Acetylated derivative of glaucine inhibits joint inflammation in collagenase-induced arthritis. (February 2015) - Gyurkovska, Valeriya; Philipov, Stefan; Kostova, Nadezhda; Ivanovska, Nina
Abstract Context: Osteoarthritis (OA) has become by far the most common joint disorder. A number of studies using OA animal models have explored the effects of agents that can modulate bone metabolism. Objective: In the present study, we investigated the effect of acetylated derivative of plant alkaloid glaucine (ADG) on experimental OA in mice. Materials and methods: Arthritis was induced by two intraarticular (i.a.) injections of collaganase. Histopathological changes were observed through hematoxylin and eosine (H&E), safranin O and toluidine blue staining. Differentiation of bone marrow (BM) cells was evaluated by tartarate-resistant acid phosphatase (TRAP) assay. The expression of phospho-Janus kinase 2 (pJAK2) and phospho signal transducer and activator of transcription3 (pSTAT3) expression in the joints was determined by immunohistochemistry. Results: We established that ADG significantly decreased cell infiltration (2.32 ± 0.14 versus 1.62 ± 0.13), cartilage loss (2.42 ± 0.12 versus 1.12 ± 0.10) and bone erosion (1.76 ± 0.13 versus 1.04 ± 0.14) in arthritic mice. It appeared that the substance inhibited in a dose-dependent manner osteoclast differentiation in vitro. ADG suppressed the expression of pJAK2 in the joint and partially affected the expression of pSTAT3. Conclusion: Present results suggest that ADG is a suitable candidate for further development as an anti-arthritic agent.